Effects of different reclamation practices on cotton root morphological characteristics and yield in coastal saline land - Li, Jingsong; Feng, Xiaohui; Li, Xiaoguang; Liu, Xiaojing; Fan, Fengcui; Guo, Kai (Frontiers in Plant Science, 2025)
Plastic mulching (PM), straw interlayer (SI), and organic amendment (OA) have been reported to effectively increase cotton yield in coastal saline lands with dry climates. However, the adaptation of cotton roots to changes in soil physical and chemical properties remains unclear. In this study, a field experiment on rain-fed cotton (Gossypium hirsutum L.) under different reclamation practices was conducted in Bohai coastal land, China. Soil structure [mean weight diameter (MWD) and bulk density (BD)], nutrients, soil water, and salt profiles were examined in relation to cotton root distribution, morphological traits [root length density (RLD), root surface area (RSA), root volume (RV), and root average diameter (RAD)], and root diameter proportions. The results showed that PM increased 7.42% soil water content and reduced 52.06% salt content in the 0–10 cm soil. These soil environment changes led to 21.21% increase in RLD, but 16.56% decrease in RAD, mainly due to an increase in the percentage of fine root (diameter < 1.0 mm) from 72.5% [control (CK)] to 83.7%; SI decreased 45.36% topsoil salt content and improved 31.28% cotton yield, but it had no significant impact on root morphological traits; OA significantly improved soil structure (64.37% increase in MWD and 9.56% decrease in BD) and nutrient properties, as well as reduced 25.73% soil salt content. Compared with PM and SI, OA showed greater promotion on RLD (60.61%), RSA (69.57%), and RV (25.37%), but had little influence on RAD. A structural equation model indicated that fine roots contributed to the increase in cotton yield and were promoted by soil water, structure, and nutrients, while being negatively correlated with soil salinity. In contrast, coarse roots (diameter > 1.0 mm) were positively correlated with soil salt content. These findings suggest that cotton plants can mitigate salt stress by optimizing root foraging in the most favorable soil zones, allocating more fine root growth to areas with higher moisture, greater nutrients, better soil structure, and lower salt content. The composition of root diameter was primarily determined by soil water and salt content rather than soil structure or nutrients. This root morphological response to the soil environment is significant for cotton production in coastal saline lands.